Implementation of witness privilege by minors in criminal procedure in the Republic of Belarus - Petrova, Olga V. (Journal of the Belarusian State University. Law, 2025)
The author of the article defines the essence of witness immunity, witness privilege. The history of this institution development is described, the features of the right implementation during investigative actions and court hearings are determined. The issue of tactical features of explanation of the right to a minor is revealed. The features of the implementation of witness privilege in domestic violence cases are clarified. The significance of witness privilege in the legal status of minor witness and victim is highlighted.
Keywords: testimony immunity; witness privilege; interviewing; minor; readings; criminal procedure